Race and Sex Differences in Correlates of Systolic Blood Pressure in Community-Dwelling Older Adults - Ford, Cassandra D. (J Health Dispar Res Pract, 2014)
OBJECTIVES: To describe correlates of measured systolic blood pressure (SBP) among community-dwelling older African American and White Medicare beneficiaries. METHODS: Participants completed an in-home assessment and factors significantly correlated with SBP were tested using multivariable models. RESULTS: Among the 958 participants (mean age= 75.3 [SD = 6.8]; 49% African American; 49% female; 52% rural) African Americans were more often diagnosed with hypertension, more likely on anti-hypertensives, and on more anti-hypertensive medications. SBP was 2.7 mmHg higher in African Americans than Whites (p=.03). SBP was higher in women than men. Multivariable models revealed differences in the factors associated with SBP by race/sex specific groups. Having a history of smoking and reports of being relaxed and free of tension were associated with higher SBP among African American men. DISCUSSION: Although more likely prescribed anti-hypertensives, mean SBP was higher for older African Americans than Whites. Results support the hypothesis that behavioral and psychosocial factors are more important correlates of SBP levels among older African Americans than among Whites.